Exploring the Co-development of Reading Fluency and Reading Comprehension: A Twin Study - Little, Callie W. (Child Dev, 2016)
The present study explores the co-development of two related but separate reading skills, reading fluency and reading comprehension, across grades 1–4. A bivariate biometric dual change score model was applied to longitudinal data collected from 1784 twin pairs between the ages of 6 and 10 years. Grade 1 skills were influenced by highly overlapping genetic and environmental factors. Growth in both skills was influenced by highly overlapping shared environmental factors. Cross-lagged parameters indicated bidirectional effects, with stronger effects from fluency to comprehension change than from comprehension to fluency change.